Sustainability: An Open Letter to our Authors and Readers - Paz-Pacheco, Elizabeth (Journal of the ASEAN Federation of Endocrine Societies, 2024)
The Journal of the ASEAN Federation of Endocrine Societies (JAFES) stands at a crucial juncture as we navigate the evolving landscape of academic publishing. Our commitment to open access publishing has fostered a rich environment for enhancing research and collaboration. This accessibility is vital for advancing the field of endocrinology in our region, where disparities in healthcare resources often limit access to essential research findings. However, maintaining the quality and accessibility of our journal requires a sustainable financial model that supports our operational needs. The costs associated with editorial management, peer review, and online hosting are substantial.